Minimal Access Surgery for Repair of Congenital Diaphragmatic Hernia: Is it Advantageous?—An Open Review - Vijfhuize, S.; Deden, A. C.; Costerus, S. A.; Sloots, C. E. J.; Wijnen, R. M. H. (European Journal of Pediatric Surgery, 2012)
Introduction Congenital diaphragmatic hernia (CDH) is a congenital life-threatening condition requiring surgical repair in the neonatal period. Minimal access surgery (MAS) is gaining ground on the classical open approach by laparotomy or thoracotomy as it minimizes damage to the abdominal or thoracic wall. Using an open review of the literature, we aimed to determine whether MAS is safe and effective in treating CDH. Furthermore, we provide selection criteria for the optimal surgical approach, laid down in a decision algorithm.Methods An online search of MEDLINE was performed (May 2012), followed by a citations search. All study types except case reports describing open and/or MAS repair of Bochdalek CDH were eligible. Primary outcome data, for example, surgical complications and mortality, were recorded, as well as secondary outcome measures, for example, operative time, duration of postoperative ventilation, tolerance of enteral nutrition, and total length of stay (LOS) in hospital. Analysis was performed in accordance with the standards of the Cochrane Handbook for Systematic Reviews of Interventions.Results We identified 15 relevant studies, 5 of them describing MAS only and 10 comparing MAS to open repair of CDH. Numbers of included patients and selection criteria for MAS varied widely. Most studies have methodological limitations, such as the use of retrospective data or historical control groups. ECMO treatment and patch use were more frequent in the open repair group (both p < 0.0001). Recurrence risk seemed to be increased in the MAS group. The need for conversion in MAS series ranged widely, from 3.4 to 75.0%. The risk of general surgical complications did not vary between groups. Mortality seemed to be less in the MAS group. Operative time seemed to be longer in the MAS group. Duration of postoperative ventilation and total LOS appeared to be reduced in this group and patients returned quicker to enteral nutrition.Conclusions We demonstrate that MAS for diaphragmatic hernia appears to be safe in terms of complications and mortality. Besides, it is associated with faster postoperative recovery. Growing experience with this technique is expected to lower the recurrence risk and to shorten the operative time. These findings should be interpreted cautiously because of methodological limitations of the studies included. Selection criteria used in various studies are associated with an important risk of selection bias. Nonetheless, these criteria can be used to identify patients who will benefit most from MAS.
Keywords: congenital diaphragmatic hernia; neonates; minimal access surgery; open repair